The effects of MEK and PKA inhibition on Spire proteins during oocyte maturation: Actin nucleation in oocytes - Tepekoy, Filiz; Akkoyunlu, Gokhan (Cellular and Molecular Biology, 2023)
Asymmetric division of oocytes driven by chromosome migration is a crucial step of oocyte maturation. Actin filaments take key roles in chromosome migration in oocytesThe aim of this study was to determine the effects of MEK and PKA inhibition on the levels of Spire-1 and Spire-2 proteins that are known to be related to actin nucleation.MEK inhibitor PD98059 and PKA inhibitor H89 were applied during IVM to the oocytes retrieved from preovulatory ovarian follicles of PMSG induced 3-5 weeks old female BalbC mice. GVBD and PBE rates were determined. Spire-1 and Spire-2 proteins were detected by immunofluorescence and western blot in oocytes at different maturation stages.Though GVBD rates were similar in different groups, PBE rates were lower in the MEK inhibition group. Through immunofluorescence, cortical localizations of Spire-1 and Spire-2 were determined. MEK inhibition resulted in a decrease in cortical Spire-1 and Spire-2 levels in PBE oocytes. PKA inhibition led to an increase in cortical Spire-1 levels in spindle migration stage oocytes, and an increase in cortical and total Spire-2 levels in PBE oocytes. Application of both MEK and PKA inhibition resulted in compensation of the decrease in Spire-1, while Spire-2 levels remained low with no compensation of PKA inhibition.According to the results of this study, chemical inhibition of MEK and PKA during oocyte maturation alters Spire-1 and Spire-2 protein levels.